A cross‐sectional study of dentine sensitivity in periodontitis patients in Trinidad and Tobago. Issue 4 (4th February 2016) - Ramlogan, S; Raman, V; Rees, JS; Legall, G
Abstract: Objective: This cross‐sectional study aimed to determine the prevalence, distribution and associated factors of dentine sensitivity (DS) among periodontitis patients in Trinidad. Methods: Sequential patients meeting the periodontitis criteria (BPE 4/4*) were included and completed a questionnaire on DS prior to a full periodontal examination. Clinically elicited symptoms of DS and presence of cervical tooth wear were recorded. Results: DS prevalence was 73.1% ( n = 130; mean age 50 years). Mean number of sensitive teeth increased with increased severity of gingival recession. Most common initiating factors of DS were cold stimuli (70.5%), brushing (25.3%) and sour food (11.6%). Correlations were obtained for DS and race, toothbrush texture hardness, cervical tooth wear and gingival recession severity ( P < 0.05; binary logistic regression). Cervical tooth wear was recorded in 46.3% of DS patients. Full‐mouth plaque scores (FMPS) and full‐mouth bleeding scores (FMBS) were statistically significantly ( P < 0.05; Mann–Whitney U ) test lower for DS versus non‐DS patients. Patients reported a low usage (27.4%) and satisfaction (53.8%) rating for desensitizing agents. Conclusions: The high prevalence of DS was comparable to other studies on periodontitis patients. Progressive periodontal disease and toothbrush abrasion were possible aetiological factors for DS in this study. Knowledge of local dietary practices and the role of acidic (sour) foods in eliciting DS may aid in management. The high prevalence of cervical tooth wear and the lower FMPS and FMBS among DS patients may reflect more aggressive tooth brushing. DS does not seem to be a limitation to plaque control in DS versus non‐DS patients in this study.